Cognitive Strategy Training in Childhood-Onset Movement Disorders: Replication Across Therapists - Gimeno, Hortensia; Polatajko, Helene J.; Lin, Jean-Pierre; Cornelius, Victoria; Brown, Richard G. (Frontiers in Pediatrics, 2021)
Objective: To explore preliminary effectiveness of the Cognitive Orientation to daily Occupational Performance (CO-OP) Approach in improving outcomes in childhood-onset Hyperkinetic Movement Disorders (HMD) including dyskinetic cerebral palsy following deep brain stimulation (DBS) across UK clinical occupational therapists. Methods: Randomised, multiple baseline, Single Case Experimental Design (SCED) N-of-1 trial with replications across participants. Five self-selected goals were identified: three goals were worked on during CO-OP and two goals were left untreated and used to assess skills transfer. Participants were between 6-21 years, had received DBS surgery with baseline Manual Ability Classification System (MACS) levels I-IV. Participants were randomized to typical or extended baseline (2 vs 6 weeks), followed by 10 weekly individual CO-OP sessions. The primary outcome was functional performance measured by the Performance Quality Rating Scale-Individualized (PQRS-I), assessed before, during and following treatment. Outcome assessors were blinded to baseline allocation, session number and assessment time. A non-overlapping index, Tau-U, was used to measure effect size. Results: Of the 12 participants recruited, 10 commenced and completed treatment. In total, 63% of trained goals improved with effect sizes 0·66 – 1·00 (‘moderate’ to ‘large’ effect), seen for all children in at least one goal. Skills transfer was found in 37% of the untrained goals in six participants. Conclusions: Cognitive strategy use improved participant-selected functional goals in childhood-onset HMD, more than just practice during baseline. Preliminary effectiveness is shown when the intervention is delivered in clinical practice by different therapists in routine clinical settings.